The Image of Father Józef Jarzębowski (1897-1964) - a Pedagogue, Soldier, Priest, Scholar and a Poet, Presented in Polish Emigration Magazines - Jolanta Chwastyk-Kowalczyk (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The article presents activities of the Polish Marist, father Józef Jarzębowski (1897-1964) - the great visionary, regarded pedagogue and the friend of children and youth. Father Jarzębowski actively participated in the Polish-Soviet War that took place in 1920. After Warsaw collapsed in 1939 he managed to go to Lithuania, from where he travelled through Siberia, Japan and the USA to finally reach Mexico. From the half of 1946, he performed the function of the director in Polish Junior High School in Santa Rosa, a Polish estate in Mexico. Having spent some time in Mexico, he visited Rome for a short period of time, from where he was sent to Great Britain. His task was to create a Polish church school for males in Fawley Court. In 1986, the school was converted into a Polish-English education centre. In 2012, the terrain on which Fawley Court stands was illegally sold by the Marists who managed the school. Provided that this unique school was built and organised by Poles and the students' parents altogether, all of them began to fight for their rights to the property. Since 2008, there is a struggle between Marists and the students who attended the school, led by Mirosław Malevski, along with their parents and all Poles.